Djibouti : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2004)
The attached Joint Staff Assessment (JSA) of the Poverty Reduction Strategy Paper (PRSP) on Djibouti reviews poverty reduction objectives and strategies. The authorities invested considerable effort in building national ownership of the PRSP by strengthening the institutional framework. The authorities made a special effort toward filling the knowledge gap on poverty that was identified in the I-PRSP. The staff of the World Bank and the IMF considers that Djibouti's poverty reduction strategy outlined in the PRSP provides a sound basis for IMF and the International Development Association (IDA) concessional assistance.